Tree Diversity Conservation Initiatives in Sacred Groves of Kathmandu Valley, Nepal - Shrestha, Laxmi Joshi; Devkota, Mohan; Sharma, Bhuvan Keshar (Nepal Journal of Science and Technology, 2020)
The study was conducted in two sacred groves of Kathmandu Valley, Pashupati Sacred Grove, and Bajrabarahi Sacred Grove, aiming to analyze the diversity of tree species and their role in conserving biodiversity. Parallel transects with concentric circular plot survey methods were applied for data collection. During the study, 23 tree species belonging to 22 genera and 15 families were recorded in Pashupati sacred grove, whereas only 19 tree species belonging to 16 genera and 13 families were recorded from Bajrabarahi Sacred Grove. The Shannon-Weiner diversity indices were higher (H=1.91) in Pashupati Sacred Grove compared to Bajrabarahi Sacred Grove, with 1.80 Shanon-Weiner Indices. Three types of forest were recorded from Pashupati Sacred Grove, namely the Schima-Pyrus forest, Myrsine-Persea forest, and Quercus-Myrsine forest, and only one Neolitsia cuipala forest from Bajrabarahi Sacred Grove. The sacred grove is one of the pioneers and community-based management regimes of the forest resource management system. It plays a decisive role in biodiversity conservation as it associated with many taboos and belief systems, thus providing a better opportunity for conservation compared to that of the government management system.